2011
DOI: 10.1111/j.1463-6395.2011.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Geometric morphometrics of carapace ofMacrobrachium australe(Crustacea: Palaemonidae) from Reunion Island

Abstract: Zimmermann, G., Bosc, P., Valade, P., Cornette, R., Améziane, N. and Debat, V. 2012. Geometric morphometrics of carapace of Macrobrachium australe (Crustacea: Palaemonidae) from Reunion Island. -Acta Zoologica (Stockholm) 93: 492-500.We investigated the structure of carapace shape variation in six populations of Macrobrachium australe Guérin-Méneville 1838 (Crustacea: Decapoda: Palaemonidae) from Reunion Island (Indian Ocean) freshwaters. The morphometric analysis revealed the occurrence of two morphotypes cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Fishing efficiency can also explain that we observed weak preferences for A. innocous , which is an excellent swimmer and very reactive in the presence of predators (Covich et al ., ; Hein and Crowl, ) or when disturbed by electrofishing (Fiévet et al ., ). Regarding the shrimp M. australe , its weak regional preferences can be explained by its sheltering behaviour during the day and variation due to its morphological plasticity (Zimmermann et al ., ). The grouping of juveniles of different species of Macrobrachium is probably not very appropriate because we observed that the adults of M. faustinum and M. heterochirus have different preferences (forces and directions) regarding velocity and depth.…”
Section: Discussionmentioning
confidence: 97%
“…Fishing efficiency can also explain that we observed weak preferences for A. innocous , which is an excellent swimmer and very reactive in the presence of predators (Covich et al ., ; Hein and Crowl, ) or when disturbed by electrofishing (Fiévet et al ., ). Regarding the shrimp M. australe , its weak regional preferences can be explained by its sheltering behaviour during the day and variation due to its morphological plasticity (Zimmermann et al ., ). The grouping of juveniles of different species of Macrobrachium is probably not very appropriate because we observed that the adults of M. faustinum and M. heterochirus have different preferences (forces and directions) regarding velocity and depth.…”
Section: Discussionmentioning
confidence: 97%
“…A pattern of shape variation according to water velocity was reported by Giri & Loy () for A. neuquensis and Zimmermann et al . () for Macrobrachium australe . In the present study, considering the whole population, we did not find any environmental pattern in A. uruguayana .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used GM to compare populations of several species of freshwater decapods (Giri and Collins 2004;Giri and Loy 2008;Barrı´a et al 2011;Idaszkin et al 2013). However, the use of GM to study prawns is still rare (Bissaro et al 2012;Zimmermann et al 2012).…”
Section: Introductionmentioning
confidence: 99%